Pruritogenic molecules in the skin of patients with dermatomyositis - Vincze, Anett; Herczeg-Lisztes, Erika; Szabó, Katalin; Béldi, Tibor Gábor; Nagy-Vincze, Melinda; Pór, Ágnes; Varga, József; Dankó, Katalin; Biró, Tamás; Tóth, Balázs István; Griger, Zoltán (Frontiers in Medicine, 2023)
Introduction: Pruritus is a common excruciating symptom in systemic autoimmune diseases like dermatomyositis (DM) but pathogenesis is not fully understood. We intended to investigate targeted expression analysis of candidate molecules involved in the development of pruritus in lesional versus non-lesional skin samples of patients affected with active DM. We looked for correlations between the investigated pruriceptive signaling molecules, disease activity and itching sensation of DM patients. Methods: Interleukins (IL-33, IL-6), tumor necrosis factor α (TNF-α), peroxisome proliferator-activated receptor γ (PPAR-γ) and ion channels belonging to the transient receptor potential (TRP) family were analyzed. The expression of TNF-α, PPAR-γ, IL-33, IL-6 and TRP channels in lesional DM skin was evaluated by RT-qPCR and immunohistochemistry and was compared with non-lesional DM skin samples. Pruritus, disease activity and damage of DM was evaluated by the 5-D itch scale and Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI), respectively. Statistical analysis was performed with IBM SPSS 28 software. Results: Seventeen active DM patients participated in the study. We could show that itching score was positively correlated with CDASI activity score (Kendall’s tau-b=0.571; p=0.003). TNF-α gene expression was significantly higher in lesional DM skin than non-lesional DM skin (p=0.009) and differed in the subgroups of patients with different itch intensity (p=0.038). The mRNA expression of lesional IL-6 correlated positively with 5-D itch and CDASI activity score (Kendall’s tau-b= 0.585; p=0.008 and 0.45; p=0.013, respectively). TRPV4 expressions were positively correlated with CDASI damage score (Kendall’s tau-b= 0.626; p<0.001), but the mRNA expressions of the TRP family, PPAR-γ, IL-6 and IL-33 were not different in lesional and non-lesional samples. Immunohistochemistry analysis did not find significant alterations in the expressions of TNF-α, PPAR-γ, IL-6 and IL-33 in lesional and non-lesional regions. Discussion: Our results argue for that cutaneous disease activity, TNF-α and IL-6 might play a central role in DM-associated itch, while TRPV4 in tissue regeneration.